Agriculture Traditionnelle Et Échecs Des Politiques De Gestion Des Aires Protégées En Côte d’Ivoire : Le Cas De La Réserve De Lamto - N’goran Ahou Suzanne (European Scientific Journal, ESJ, 2016)
From more than 16 million hectares of forest in the 1960s, Côte d’Ivoire now disposes of less than 2 million hectares left. In fact, the farming has rapidly back away vegetal resources. Even protected areas such as the reserve of Lamto, created to ensure the conservation of vital sample representative of biodiversity are threatened by agricultural activities in such a way that their management remains problematic. The reserve of Lamto is a delicate protected area throughout its size and its localization; for it has a modest surface of 2,500 hectares and it is situated in a zone that has contact with the forest and the savanna what the ecologists qualify as a delicate ecosystem. Moreover it is surrounded by an important riverside population whose main activity is farming. It is about a diversified farming but traditional itinerant on burning with elementary working tools and strongly dependant on the climate. In short, it is a space consuming farming. Today, the increasing demand of farming area leads the riverside population to exercise a heavy pressure on the reserve whence the menace of the failure of its political management.